Implementasi Telegram untuk Budidaya Lumbricus Rubellus Berbasis IoT - Ari Sugiharto; Satyo Nuryadi; Bagus Angga Wicaksana (Jurnal Elektronika dan Teknik Informatika Terapan ( JENTIK ), 2023)
Lumbricus Rubellus (earthworm) has various benefits: serving as livestock feed, medicine, cosmetics ingredients, and organic fertilizer from vermicompost. Earthworm cultivation is not difficult, but requires extra monitoring due to various challenges that affect their growth and development. One key factor to consider is the weather, as prolonged hot temperatures during droughts can disrupt the growth of earthworms. To address this challenge, a monitoring and control device was designed to regulate the temperature and humidity of the cultivation area automatically. Additionally, the device provides information about the age of the cultivated earthworms for predicting the harvesting period. These functions were realized by utilizing various sensors, such as the DHT11 sensor for room temperature measurement with 95.05% accuracy and the Soil Moisture sensor for soil humidity measurement with 96.3% accuracy. Furthermore, a fan and water pump were employed to automate temperature and humidity regulation. The main control unit for this system is the NodeMCU ESP8266. Telegram application was used as a platform to monitor and control this IoT-based device remotely. With this device, the process of earthworm cultivation is expected to be more accessible.